Análise epidemiológica e temporal da hanseníase na Paraíba - Brito, Karen Krystine Gonçalves de (2014)
Introduction: Leprosy is an infectious and contagious disease, chronic, disabling, with high infectiousness and low morbidity, which affects the nerve endings, from which the number of complications and secondary lesions intensify, leading to the appearance of deformities, disabilities, limitation or restriction of activities in social participation. It is considered a notifiable disease in Brazil, and its epidemiological aspects of expressing one of the main factors to treat it as a public health problem. The development of this research aims to contribute to the clarification of the epidemiological situation of leprosy in the State of Paraíba, as well as to subsidize the planning of actions aiming to contain and minimize the negative effects of endemic disease in this population. Objectives: Analyzing the association between socio-demographic variables and clinical-epidemiological and temporal series 2001-2006 and 2007-2011, for patients with Hansen's disease in the State of Paraíba; characterize the temporal evolution, according to epidemiological and operational indicators of leprosy endemic in the State of Paraíba in the period from 2001 to 2011; characterize the association between socio-demographic variables and clinics according to detection of case by contact exam and/or spontaneous search. Methods: This was an epidemiological study of temporal time series, retrospective and documentary base; from the leprosy cases reported and residents in the State of Paraíba between 2001 and 2011. The data of secondary character were obtained through the State Department of Health (SES) located in the city of João Pessoa / Paraíba. The research is part of a larger project approved by the Ethics Committee of CCS / UFPB in a report Protocol n° 203.485, CAAE 11076312.1.0000.5188. The information was stored in a database, using the Statistical Package Program for Social Sciences (SPSS) version 20.0, and analyzed with techniques of inferential statistics. The significance level for all analysis was of 5% (p < 0.05). Results: The survey consisted of 10.476 cases of leprosy in Sinan, of which 6,161 in P1 (2001-2006) and 4,315 in P2 (2007-2011), which is the principle a reduction of 42.7 % of cases among the periods. The results point to an association (p < 0.05) between the measured variables and the time cutouts. Between 2001 and 2011 there was a decrease in cases under 15 years, reversal of male to female predominance, fall in cases with low education, increase in the number of injuries and affected nerves as well as the number of abandonment cases. As for the indicators established by the Ministry of Health is perceived by a coefficient 100.000/hab very high endemicity, average effectiveness in the early detection of cases and parameters of precariousness in the evaluation of service quality. Between 2001 and 2011 there was a decrease in cases under 15 years, reversal of male to female predominance, fall in cases with low education, increase in the number of injuries and affected nerves as well as the number of abandonment cases. Relevant to the factors that are associated to the development of the disease it appears that only the variables level of education and of disability show significant association (p > 0.05) with the form of detection of the disease. Conclusion: In general, it was permissible to fleshing out many descriptive aspects involving leprosy endemic in Paraíba, in order to facilitate or simply promote a broader look about the need for works that focus the priorities of our municipality, with a view to obtaining an increasingly significant improvement to the current epidemiological situation.